RISK FACTORS FOR HEALTHCARE-ASSOCIATED INFECTIONS IN INTENSIVE CARE UNITS - Marcia Cardoso Teixeira Sinésio; Marcia Cristina da Silva Magro; Tatiane Aguiar Carneiro; Kamilla Grasielle Nunes da Silva (Universidade Federal do Paraná, 2018)
Objective: to identify patients and risk factors related to the occurrence of healthcare-associated infectionsin intensive care units. Method: cross-sectional study with 155 hospitalized patients between 2012 and 2014 in two intensive care units of two public hospitals of the Federal District. Data were collected from the medical records and recorded in a spreadsheet using the Microsoft Excel® program. Results with p-value <0.05 were considered significant. Results: of the total of 155 patients, 55 (35.5%) patients were affected by healthcare-associated infections during hospitalization in the intensive care unit. Length of stay (p=0.001), hospitalization due to clinical causes (p=0.017), diabetes mellitus (p=0.002) and elective surgery (p=0.011) were independent risk factors for these infections. Conclusion: infectious complications affected approximately one third of the patients in the intensive care setting. Surveillance of these complications may guide actions to improve the safety of critical patients.